Preliminary results of determining the social variables of rural population's vulnerability to climate change (Mongolian Journal of Geography and Geoecology, 2023)
Mongolia is extremely vulnerable to climate change due to its geographical location, fragile ecosystem, and economic system dependent on nature and climate. Especially, rural people and herders in Mongolia are a social group that is very sensitive and vulnerable to climate change. This study aimed to define the condition of the social and economic vulnerability of rural people to climate change at the soum level in the Bayankhongor, Dundgovi, and Khovd provinces. Socioeconomic data were collected in a continuous series for the last 10 years. Socioeconomic variables of the vulnerability to climate change were calculated and thematic images were created using ArcGIS for each soum of three provinces for comparison of the provincial average. As a result, we identified 8 major social variables including rural poverty; unemployment rate; dependency ratio; population growth and migration (the average annual growth rate of the population and the net migration rate); education level of the rural population; share of male/female headed household in total household; death rate from cardiovascular diseases; and supply of doctors and specialists (number of physicians per 10,000 people). In the future, the study can be further explored by understanding the interrelationships and correlations between social variables of vulnerability and vulnerability assessment. The results can be used for the implementation of climate change adaptation strategies at the local level, and the development of science-based policies can be supported.Хөдөөгийн иргэдийн уур амьсгалын өөрчлөлтөд нийгмийн эмзэг байдлын хувьсагчуудад дүн шинжилгээ хийсэн урьдчилсан үр дүнгээсХУРААНГУЙ: Байгаль, газарзүйн нөхцөл, цаг уураас хараат эдийн засгийн тогтолцоо зэргээсээ шалтгаалан уур амьсгалын өөрчлөлтөд өртөмтгий орнуудын нэг нь манай улс бөгөөд хөдөөгийн иргэд, малчид нь уур амьсгалын өөрчлөлтөд нэн эмзэг нийгмийн бүлэг юм. Энэхүү судалгаа нь Баянхонгор, Дундговь болон Ховд аймгуудын сумдын жишээгээр уур амьсгалын өөрчлөлтөд хөдөөгийн иргэд, тэр дундаа малчдын нийгмийн эмзэг байдлыг тодорхойлох зорилготой. Дэвшүүлсэн зорилго, зорилтдоо хүрэхийн тулд судалгааны бүс нутгийн сумдын түвшинд хүн ам, нийгмийн шалгуур үзүүлэлтүүдийг сүүлийн 10 жилийн тасралтгүй цуваагаар цуглуулан, аймгийн дундажтай харьцуулах замаар боловсруулалт хийж, түүндээ тулгуурлан ArcGIS программ дээр сэдэвчилсэн зургууд зохиосон. Үүний дүнд бид хөдөөгийн ядуурал, ажилгүйдлийн түвшин, хүн ам зүйн ачаалал, хүн амын өсөлт ба шилжилт хөдөлгөөн (хүн амын жилийн дундаж өсөлт ба шилжилт хөдөлгөөний цэвэр коэффициент), хөдөөгийн хүн амын боловсролын түвшин, өрх толгойлсон эрэгтэй/эмэгтэй тэргүүлэгчтэй өрхийн эзлэх хувь, зүрх судасны өвчнөөр нас баралтын түвшин, эмч, мэргэжилтний хангамж (10000 хүнд ногдох эмчийн тоо) зэрэг нийгмийн эмзэг байдлын 8 гол хувьсагчдыг тодорхойллоо. Цаашид тус судалгааг улам гүнзгийрүүлэн, уур амьсгалын өөрчлөлтөд эмзэг байдлын нийгмийн хувьсагчид хоорондын харилцан хамаарал, уялдаа холбоог судлан, чанарын судалгаагаар үр дүнг баталгаажуулж, орон нутгийн түвшинд уур амьсгалын өөрчлөлтөд дасан зохицох стратеги хэрэгжүүлэх, шинжлэх ухаанд суурилсан бодлого боловсруулахад дэмжлэг үзүүлэх зөвлөмж боловсруулах боломжтой.Түлхүүр үгс: Уур амьсгалын өөрчлөлт, эмзэг байдал, хөдөөгийн иргэд, нийгмийн хувьсагч